Child Free Vis a Vis Al Walud in the Perspective of Hadith - Umu Solikhah; Badrudin Badrudin; Lalu Turjiman Ahmad (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This research examines the phenomenon of Child free vis-à-vis the concept of Al Walud from the perspective of Hadith, investigating how Islamic teachings on reproduction and family can be interpreted in a modern context. Through analysis of relevant hadiths and contemporary literature, this study reveals space for reinterpretation that allows the integration of the Child free concept into Islamic understanding. The results show that a contextual approach to hadith and the use of maqasid al-shariah methodology can bridge traditional and modern understandings. The social, economic, and spiritual implications of this shift in understanding are discussed, along with challenges and opportunities in harmonizing both concepts. This research contributes to the development of contemporary fiqh that is more responsive to global realities while upholding fundamental Islamic values.